SECURE ROUTING PROTOCOL IN WSN AGAINST VAMPIRE ATTACKS - C. Nalini, G Lakshmi Vara Prasad (International Journal of Modern Agriculture, 2020)
Wireless Sensor Networks (WSNs) in today’s world are the means of communication. These contain nodes that act as transmitter and receivers are prone to different attacks leading to different types of losses. The resource depletion attack that is called vampire attack drains out the energy from the nodes leaving them useless. These attacks are protocol compliant, they are easy to implement. Since they are orthogonal in nature they can easily intrude into any routing protocol. They affect the entire network causing large loss of energy. The proposed method detects the presence of vampire attack and the simulation results show the energy consumption in each case.